Fallopian canal arachnoid cyst with acute facial nerve paralysis in children: a report of two cases and literature review - Sun, Jianbin; Han, Weiju (Frontiers in Neurology, 2023)
Introduction Symptoms induced by arachnoid cysts in the fallopian canal are uncommon, and facial nerve paralysis without cerebrospinal fluid otorrhea is comparatively rarer. Methods Herein, we present two cases of arachnoid cysts in the fallopian canal with acute severe facial nerve paralysis and review the relevant literature. Results The symptoms and imaging findings of these two cases resembled those of facial nerve schwannomas. Cerebrospinal fluid otorrhea occurred upon removal of the arachnoid cyst, and the facial nerve was observed to be separated into multiple filaments or compressed and atrophied. Facial-hypoglossal nerve anastomosis and decompression were conducted after packing the dehiscence of cerebrospinal fluid otorrhea for the two cases. Conclusion Arachnoid cysts of the fallopian canal rarely cause facial nerve paralysis. Enhanced magnetic resonance imaging is vital for differentiating schwannomas. Different treatment strategies should be adopted for patients with different degrees of facial nerve paralysis; however, concurrent repair of cerebrospinal fluid otorrhea and facial nerves during surgery can occasionally be challenging.